Atribut Produk, Harga Word Of Mouth Communication terhadap Keputusan Pembelian Produk Smartphone - Muhammad Ihsan; Yon Rizal; Albet Maydiantoro (JEE (Jurnal Edukasi Ekobis), 2018)
Research aims to find out the influence of products attribute, prices, and word of mouth communication of the product purchase decision of vivo smartphone. The methods used is descriptive of verification method with the approach ex post facto capital. The population is the students of PIPS academic year of 2015-2017, FKIP University Lampung. The sample of collecting technique used is non probability of sampling with the accidental sampling method. The sample used is from 60 respondents. The results of the study showed that there was some influence simultaneously products attribute, prices, and word of mouth communication of the product purchase decision of vivo smartphone on student PIPS FKIP University Lampung. Based on the analysis it was obtained fhitung 77.249 ftabel 2.77 this demonstrates with multiple linear regression coefficient of determination ( r2 ) 0.805 which means the purchase decision influenced by product attributes, prices, and word of mouth communication as much as 80.5 % and 19.5 % influenced by other factors. Penelitian ini bertujuan untuk mengetahui pengaruh atribut produk, harga dan word of mouth communication terhadap keputusan pembelian produk smartphone vivo. Metode yang digunakan adalah metode deskriptif verifikatif dengan pendekatan ex post facto. Populasi adalah mahasiswa jurusan PIPS angkatan 2015-2017, FKIP Universitas Lampung. Teknik pengambilan sampel menggunakan non probability sampling dengan metode accidental sampling. Jumlah sampel yang digunakan sebanyak 60 responden. Hasil penelitian menunjukan bahwa ada pengaruh secara simultan atribut produk, harga dan word of mouth communication terhadap keputusan pembelian smartphone vivo pada mahasiswa jurusan P. IPS FKIP Universitas Lampung. Berdasarkan analisis diperoleh Fhitung  77,249 Ftabel  2,77 yang ditunjukan dengan regresi linier multiple dengan koefisien determinasi (r2) 0,805  yang berarti keputusan pembelian dipengaruhi oleh atribut produk, harga dan word of mouth communication sebesar 80,5 % dan 19,5 % dipengaruhi oleh faktor lain. Kata kunci: keputusan pembelian, atribut produk, harga, word of mouth communication